2016
DOI: 10.1177/0363546516644604
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of High School Sports-Related Injuries Resulting in Medical Disqualification

Abstract: MDQ injuries vary by sport, sex, and type of athletic activity and occur most frequently as a result of player-player contact. These findings should prompt additional research into the development, implementation, and evaluation of targeted injury prevention efforts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
44
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(47 citation statements)
references
References 17 publications
3
44
0
Order By: Relevance
“…17 In fact, the incidence of injuries among high school soccer players that resulted in medical disqualification (career-or season-ending injuries) between 2005 and 2014 was found to be 0.17 and 0.10 per 1000 athletic exposures for girls and boys, respectively. 16 Among the 11 sports evaluated, the injury rate for soccer for boys was lower only than those for football, ice hockey, and lacrosse, and for girls, only gymnastics had a greater rate of disqualifying injury. Although not as common, youth soccer players are also at risk for overuse injuries, with a recent study identifying injury rates of 0.15 and 0.20 injuries per 10 000 athletic exposures among high school male and female soccer players, respectively, with knees and lower legs being the most common locations of injury.…”
Section: Injury Types and Mechanismsmentioning
confidence: 94%
See 1 more Smart Citation
“…17 In fact, the incidence of injuries among high school soccer players that resulted in medical disqualification (career-or season-ending injuries) between 2005 and 2014 was found to be 0.17 and 0.10 per 1000 athletic exposures for girls and boys, respectively. 16 Among the 11 sports evaluated, the injury rate for soccer for boys was lower only than those for football, ice hockey, and lacrosse, and for girls, only gymnastics had a greater rate of disqualifying injury. Although not as common, youth soccer players are also at risk for overuse injuries, with a recent study identifying injury rates of 0.15 and 0.20 injuries per 10 000 athletic exposures among high school male and female soccer players, respectively, with knees and lower legs being the most common locations of injury.…”
Section: Injury Types and Mechanismsmentioning
confidence: 94%
“…The majority of youth soccer injuries are acute events resulting from player-to-player contact, with a considerably greater proportion of injuries occurring during competition than practice. 5,15,16 With respect to severe injuries (time loss .21 days), incidence remains considerably higher during games than practice, and girls demonstrate a greater incidence than boys (3.3 vs 2.5 per 1000 athletic exposures). 17 In fact, the incidence of injuries among high school soccer players that resulted in medical disqualification (career-or season-ending injuries) between 2005 and 2014 was found to be 0.17 and 0.10 per 1000 athletic exposures for girls and boys, respectively.…”
Section: Injury Types and Mechanismsmentioning
confidence: 99%
“…This is consistent with the findings from multiple previous studies of sports-related injuries, which have revealed that both injury rates and the severity of injuries are greater in competition compared with practice. 6,11,15,20,21 A common hypothesis proffered in those previous publications is that PEDIATRICS Volume 140, number 6, December 2017 5 injuries are more common during competition because of increased athlete-athlete contact and a higher intensity of play. However, future research is needed to confirm this presumption.…”
Section: Discussionmentioning
confidence: 98%
“…7 -10 The authors of a previous study found that in 5 boys' sports (baseball, basketball, ice hockey, track and field, and wrestling) and 2 girls' sports (softball and field hockey), hand or wrist fracture was 1 of the most common reasons for medical disqualification (MDQ), either for the season of for the athlete's career. 11 Despite these concerns, the literature on hand/wrist injuries has largely consisted of case reports, and, to date, little has been published to examine the rates and patterns of hand/wrist injuries among US high school athletes. 12,13 Elucidating the epidemiology of hand/wrist injuries will not only help clinicians assess the impact of such injuries on sports participation but should also help drive more effective injury prevention efforts.…”
mentioning
confidence: 99%
“…We would also like to thank the author of the letter to the editor for bringing this fact to our attention as it is a limitation of our study. However, football injuries, when compared with other contact sports injuries, have been found more likely to require surgery and to end an athlete's season or career, which speaks to the severity of these injuries [1][2][3]. Thus, it is unlikely that a significant number of these injuries would resolve so quickly; this confounding factor may account for some of the 20% observed difference in injury rate between Thursday night football and weekend games, however it is unlikely that it accounts for all of it.…”
Section: Letter To the Editormentioning
confidence: 99%